Plasma PRPC Levels Correlate With Severity and Prognosis of Intracerebral Hemorrhage - Wu, Xiaoyu; Liu, Ming; Yan, Tian; Wang, Zefan; Yu, Wenhua; Du, Quan; Hu, Wei; Zheng, Yongke; Zhang, Zuyong; Wang, Keyi; Dong, Xiaoqiao (Frontiers in Neurology, 2022)
Background Cellular prion protein (PRPC) exerts brain-protective effects. We determined the relationship between plasma PRPC levels and disease severity plus clinical outcome after acute intracerebral hemorrhage (ICH). Methods A total of 138 ICH patients and 138 healthy controls were included in this prospective, observational study. Hematoma volume and Glasgow coma scale (GCS) score were used to assess disease severity. Glasgow outcome scale (GOS) scores of 1–3 and 4–5 at 90 days after stroke were defined as a poor outcome and good outcome, respectively. Using multivariate analysis, we discerned the relation of plasma PRPC levels to disease severity and poor outcome. The receiver operating characteristic (ROC) curve was built to evaluate the prognostic predictive capability. Results Plasma PRPC levels in ICH patients were significantly higher than those in healthy controls (median, 4.20 vs. 2.02 ng/ml; P < 0.001), and were independently correlated with GCS score (r = −0.645, P < 0.001) and hematoma volume (r = 0.627, P < 0.001). Plasma PRPC levels were highly correlated with GOS score (r = −0.762, P < 0.001), and were substantially higher in patients with poor outcomes than in those with the good outcomes. Using maximum Youden index, plasma PRPC levels >3.893 ng/ml distinguished the risk of poor outcome at 90 days, with a sensitivity of 86.4% and a specificity of 65.8% (area under the curve, 0.809; 95% confidence interval (CI), 0.737–0.881, P < 0.001). Plasma PRPC levels >3.893 ng/ml were independently associated with a poor 90-day outcome with an odds ratio of 12.278 (95% CI, 5.101–29.554). Conclusion Elevated plasma PRPC levels are significantly associated with disease severity and poor 90-day outcome in ICH patients, indicating that plasma PRPC may be used as a potential prognostic biomarker after ICH.